Identificación de los atractivos y servicios turísticos de la parroquia Chuquiribamba del cantón Loja. - Guachizaca González, Diana Piedad (2018)
Loja, privileged city located south-west of Ecuador, one can say that is the main cultural historical urban southern region, achieving an important seat placed for outstanding artistic and cultural creativity, so rural parish Chuquiribamba canton with high tourist projections, thanks to its striking traditional buildings, its cultural, natural diversity and landscape endowed with unique and unrepeatable characteristics such as being surrounded by hills (Santa Barbara, Santo Domingo), hills and lush vegetation (vegetables, legumes ), which will make it become a favorite destination for tourists. Withthis backgrounddenotes the importanceof this research, which is entitled "IDENTIFICATION OFTOURISTATTRACTIONSANDSERVICESOFTHE PARISHOFCANTONChuquiribambaLoja", the samethat was fulfilledas a prerequisite o obtaining thetitleofEngineeringtourism Administrationfrom the National UniversityofLoja, andthis is intended togive a contributionto tourism developmentnot onlyin the parishbut alsothe cantonChuquiribambaLoja. The overall goal of this work is to contribute to tourism development in the parish Chuquiribamba through the identification and exploitation of existing services and attractions to boost its tourism development with a focus on social responsibility, preserving the environmental care, having as purpose the use of natural and cultural resources in a sustainable way and thus make it a tourist destination, generating financial resources and thus improve the quality of life by creating jobs. The specific objectives are: Develop a tourist diagnosis Chuquiribamba parish to know the current situation which allowed it in the first instance make an inventory of tourist attractions and services with regard to the parish together with it could identify the strengths , opportunities, weaknesses and threats and in turn the results allowed defining the second objective was to determine alternatives for the development and enhancement of attractions Chuquiribamba parish eventually became third objective socialization of the results achieved with the stakeholders for possible execution. The process began with the respective literature review, in order to deepen knowledge about the parish Chuquiribamba your general development plan, etc.. The methodology was developed based on the fulfillment of the objectives, for which we used several methods and techniques such as: interview, survey, literature collection, and the methodology used to inventory and cadastre of tourist services of the Ministry of Tourism (MINTUR) allowing successful development work, through direct observation of the attractions and tourist services has the parish. As for the results we developed a diagnostic matrix of the current situation of the parish Chuquiribamba, which collected information about the general history of the parish and conducted a field investigation to find data on it. In addition, an analysis of the tourism situation of the parish, which hosted the survey technique which was aimed at students from the National University of Loja and tourists and the interview technique which was directed to the Parish Council as which allowed us to analyze the existing tourism demand. The "Tourist Route Chuquiribamba parish aims to introduce the design of a route based on a four circuits, with less attractive offer far between, with a theme and image that actually represent the majority of its assets, with scope to provide objective, easy to use, self-guided tourists through printed promotional and signage taking aim at improving the tourism and contribute to the recognition of attractions that often go unnoticed for tourists, in the absence of adequate signage. In the present investigationit is concluded thatthenaturalsitesof the parish Chuquiribambanot have the proper infrastructure to allow easier access to them,despite having relevancies to attract tourists, their characteristics, accessibility, and conservation statusare fully orpartiallyaltered and deteriorated, thatthe cultural attractions that enhance the traditions ofthe parish and who have minimal skir mishes are conservation and development of punts,poncho sand folk customs,that there is interest, micro business sector, artisanal sector with commitment to develop people through training and tourism planning, but not have the cooperation of the general population, that the current situationof the ViaLojaChuquiribamba(and theVillonaco- Chuquiribamba) discour ages interest for visiting tourists area and thus paralyzes tourism development inthe parish, that tourism servicesare there in the parish Chuquiribambanot have the infrastructure orqualified human resources with necessary skillsto enable the tourist offer quality service characteristic of the area. At the endof this document include s annexes that supported there search.